2009
DOI: 10.1684/mrh.2009.0177
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in major depression

Abstract: There are contradictory data regarding the levels of magnesium in patients with major depression (MD) and how antidepressants influence their concentration. Our results show erythrocyte magnesium in patients with MD (44.39 ± 2.7 mg/L vs 59.1 ± 3.2 mg/L in control group, p < 0.05) and only in patients with severe MD (Hamilton score > 23) was a moderate decrease in plasmatic magnesium observed (17.7 ± 1.5 mg/L vs 22.9 ± 3.3 mg/L in control group). Therapy with antidepressants from different groups and with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 18 publications
(16 reference statements)
1
32
0
Order By: Relevance
“…Both sertraline given at 150 mg/day for 4 weeks and amitriptyline given at 75 mg/day for 4 weeks have been shown to increase Mg concentration in erythrocytes. It has been suggested that this may be a possible biochemical mechanism for the effectiveness of these drugs in some patients [75]. …”
Section: Resultsmentioning
confidence: 99%
“…Both sertraline given at 150 mg/day for 4 weeks and amitriptyline given at 75 mg/day for 4 weeks have been shown to increase Mg concentration in erythrocytes. It has been suggested that this may be a possible biochemical mechanism for the effectiveness of these drugs in some patients [75]. …”
Section: Resultsmentioning
confidence: 99%
“…38 Moreover, treatment with antidepressants (specifically, amytriptiline and sertraline) leads to a significant increase of erythrocyte Mg concentrations. 18 A recent randomized clinical trial evaluating the efficacy of oral Mg supplementation (with MgCl 2 ) in treating 23 depressed elderly patients with type 2 diabetes and hypomagnesaemia also demonstrated that MgCl 2 is as effective as imipramine 50 mg daily. 20 Since our report does not include information concerning a better outcome following Mg supplementation, we cannot substantiate a possible role of impaired Mg homeostasis in the unfavourable therapeutic course of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Mg levels in severely depressed patients have, in fact, been found to be moderately decreased. 18 An association between Mg and anhedonic features, which typically characterize major depression, has been suggested by a recent study in which Mg's (MgCl 2 0.2 mM/kg/day) influence on the reward system was tested using conditioned place preference in rats and Mg has been shown to moderately stimulate the reward system. 15 A relation between Mg and a therapeutic potential in affective disorders has been noted as early as 1921: hypodermically administered Mg sulphate caused 50 patients having agitated depression to relax and sleep from 4 to 6 hours.…”
Section: Introductionmentioning
confidence: 98%
“…Magnesium has been used for years to treat hypertension [8], eclampsia [9], and other cardiovascular [10] or nerve disorders [11] and is safe in patients with normal renal function. This pilot study was designed to evaluate the effectiveness of magnesium oxide as a natural, inexpensive, non-prescription, readily available treatment for patients experiencing hot flashes.…”
Section: Introductionmentioning
confidence: 99%